2010
DOI: 10.4103/0975-9476.74425
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anticataract potential of Triphala in selenite-induced cataract: In vitro and in vivo studies

Abstract: Triphala (TP) is composed of Emblica officinalis, Terminalia chebula, and Terminalia belerica. The present study was undertaken to evaluate its anticataract potential in vitro and in vivo in a selenite-induced experimental model of cataract. In vitro enucleated rat lenses were maintained in organ culture containing Dulbecco’s Modified Eagles Medium alone or with the addition of 100μM selenite. These served as the normal and control groups, respectively. In the test group, the medium was supplemented with selen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…In lenses from Groups III, IV, and V, which were pretreated with curcumin, CD1, and CD2, respectively, along with selenite, the SOD, and Ca 2+ ATPase activities were similar to control groups (Figure 3 and Table 2), indicating a complete reversal of selenite‐induced cataract. Our results are in agreement with the earlier reports (29–35).…”
Section: Discussionsupporting
confidence: 94%
“…In lenses from Groups III, IV, and V, which were pretreated with curcumin, CD1, and CD2, respectively, along with selenite, the SOD, and Ca 2+ ATPase activities were similar to control groups (Figure 3 and Table 2), indicating a complete reversal of selenite‐induced cataract. Our results are in agreement with the earlier reports (29–35).…”
Section: Discussionsupporting
confidence: 94%
“…Although 50% of problems were eliminated by computer shields, other methods are still needed to minimize the vision complications. A study on the effect of computer shields showed that 81% of subjects could easily read the screen, while the prevalence of tired eyes reduced from 86% to 45%, itching and watery eyes from 50% to 28%, dry eyes from 52% to 24% and headaches from 53% to 32% (34).…”
Section: Discussionmentioning
confidence: 99%
“…Six equal parts of the homogenate were made for estimation of GSH, malondialdehyde (MDA), SOD, CAT, GPX and GSH transferase. The process followed above was modified from Gupta et al [32]. …”
Section: Methodsmentioning
confidence: 99%